2018
DOI: 10.1530/ec-18-0154
|View full text |Cite
|
Sign up to set email alerts
|

SOCIETY FOR ENDOCRINOLOGY CLINICAL GUIDANCE: Inpatient management of cranial diabetes insipidus

Abstract: Cranial diabetes insipidus (CDI) is a treatable chronic condition that can potentially develop into a life-threatening medical emergency. CDI is due to the relative or absolute lack of the posterior pituitary hormone vasopressin (AVP), also known as anti-diuretic hormone. AVP deficiency results in uncontrolled diuresis. Complete deficiency can lead to polyuria exceeding 10 L/24 h. Given a functioning thirst mechanism and free access to water, patients with CDI can normally maintain adequate fluid balance throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 3 publications
(3 reference statements)
1
36
0
3
Order By: Relevance
“…DI represents a life-threatening entity when the thirst mechanism is impaired, as in cases of hypothalamic disorder or reduced consciousness or lack of water availability such as in cases of physical disability resulting in severe dehydration and death. For this reason, a Society for Endocrinology guideline has been recently issued for the in-patient management of patients with CDI [7,86].…”
Section: Central Diabetes Insipidus (Cdi)mentioning
confidence: 99%
“…DI represents a life-threatening entity when the thirst mechanism is impaired, as in cases of hypothalamic disorder or reduced consciousness or lack of water availability such as in cases of physical disability resulting in severe dehydration and death. For this reason, a Society for Endocrinology guideline has been recently issued for the in-patient management of patients with CDI [7,86].…”
Section: Central Diabetes Insipidus (Cdi)mentioning
confidence: 99%
“…-In 2018, the Society for Endocrinology (SfE) published guidelines on in-hospital management of central DI 15 . This report was prompted by a study of patients hospitalized with central DI, which showed that desmopressin treatment had been missed or delayed in 88% of admissions, and that 35% of patients consequently developed dysnatraemia 16 .…”
Section: Acute Infection With Suspected or Confirmed Covid-19mentioning
confidence: 99%
“…Further guidance for emergency management of diabetes insipidus is available from the Society for Endocrinology website. 29…”
Section: Management Of Adrenal Crisis In Adultsmentioning
confidence: 99%